High Levels of Sequence Diversity in the 5′ UTRs of Human-Specific L1 Elements. (7th February 2012) - Lee, Jungnam; Mun, Seyoung; Meyer, Thomas J.; Han, Kyudong
Abstract : Approximately 80 long interspersed element (LINE-1 or L1) copies are able to retrotranspose actively in the human genome, and these are termed retrotransposition-competent L1s. The 5′ untranslated region (UTR) of the human-specific L1 contains an internal promoter and several transcription factor binding sites. To better understand the effect of the L1 5′ UTR on the evolution of human-specific L1s, we examined this population of elements, focusing on the sequence diversity and accumulated substitutions within their 5′ UTRs. Using network analysis, we estimated the age of each L1 component (the 5′ UTR, ORF1, ORF2, and 3′ UTR). Through the comparison of the L1 components based on their estimated ages, we found that the 5′ UTR of human-specific L1s accumulates mutations at a faster rate than the other components. To further investigate the L1 5′ UTR, we examined the substitution frequency per nucleotide position among them. The results showed that the L1 5′ UTRs shared relatively conserved transcription factor binding sites, despite their high sequence diversity. Thus, we suggest that the high level of sequence diversity in the 5′ UTRs could be one of the factors controlling the number of retrotransposition-competent L1s in the human genome during the evolutionary battle between L1s and their host genomes.